2009
DOI: 10.1177/194008290900200401
|View full text |Cite
|
Sign up to set email alerts
|

Forest Recovery Following Shifting Cultivation: An Overview of Existing Research

Abstract: Shifting cultivation is a predominant practice in the majority of tropical hilly tracts. Relatively few studies have examined forest recovery following shifting cultivation and we have reviewed these studies to identify and synthesize general recovery patterns. Most studies report that, although pioneer tree species recover relatively faster, woody biomass of mature forest trees recovers several decades after suspension of cultivation. Analysis of bird-species inventories in 10 studies revealed that up to 70% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 51 publications
0
22
0
8
Order By: Relevance
“…The selected areas were then grouped into four categories, according to fallow age: young fallows (range 7-8 yrs), medium-aged fallows (range [10][11][12][13][14] were divided into ten 100 m 2 subplots [33]. A total of forty plots were surveyed, corresponding to ten mature stands and ten in each of the fallow stages.…”
Section: Site Selection and Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The selected areas were then grouped into four categories, according to fallow age: young fallows (range 7-8 yrs), medium-aged fallows (range [10][11][12][13][14] were divided into ten 100 m 2 subplots [33]. A total of forty plots were surveyed, corresponding to ten mature stands and ten in each of the fallow stages.…”
Section: Site Selection and Data Collectionmentioning
confidence: 99%
“…This agricultural system has been labeled as the most serious land use problem and a major driver of deforestation in tropical areas of Africa [9,10]. It has been, however, an ideal solution for soil fertility in the humid tropics, at least in the past when the human population density was low and fallow periods were long enough to restore soil fertility [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Community recovery can be accelerated when comparatively large forest area share a border with shifting cultivation site, in comparison with recovery in sites with shorter fallow cycles in the absence of adjoining forests, which act as sources for recolonization of vegetation [28].…”
Section: Discussionmentioning
confidence: 99%
“…It has been pointed out that large sampling scale studies incorporate the effects of surrounding habitat and therefore reflect bird diversity in the agriculture-fallow-forest matrix rather than the diversity in each habitat specifically [2]. This assumption is based on previous large-scale secondary studies indicating a negligible effect on bird diversity [e.g., [39][40][41][42], whereas other studies [19,43] have shown that diversity is affected in small-scale studies that do not make up a matrix of surrounding primary (or close to primary) habitats and edge habitats.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in bird communities may reveal successional processes going on in cleared forest. For example, analysis of bird-species inventories from 10 studies revealed that up to 70% of mature forest bird communities may recover in successional sites, and that species composition is about 55% similar to that of mature forests within 25 years [2].…”
Section: Introductionmentioning
confidence: 99%